Answers

2015-04-03T12:11:14+05:30
LHS
1+secФ/secФ⇒1/secФ+secФ/secФ⇒cosФ+1
RHS
sin²Ф/1-cosФ⇒1-cos²Ф/1-cosФ        using sin²Ф+cos²Ф=1
(1-cosФ) (1+cosФ)/1-cosФ              using a²-b²=(a-b) (a+b)
cosФ+1
LHS=RHS
Hence proved
0
i dint understood 4th step plz can u explain
ya ya i got it thank u
welcome
2015-04-03T12:26:31+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
LHS =  \frac{1+sec teta}{secteta}

= \frac{1}{secteta} +  \frac{secteta}{secteta}

= cosФ+1


RHS =  \frac{ 1-\cos^{2}teta }{1-costeta}

= \frac{(1-costeta)(1+costeta)}{1-costeta}

=cosФ+1

LHS=RHA
Hence Proved.
0